2021
DOI: 10.1111/jam.15209
|View full text |Cite
|
Sign up to set email alerts
|

Detection of unprecedented level of antibiotic resistance and identification of antibiotic resistance factors, including QRDR mutations inEscherichia coliisolated from commercial chickens from North India

Abstract: Aim: This study aimed to investigate the occurrence of antibiotic resistance phenotype and simultaneously understand its genetic basis in Escherichia coli isolated from the cloacal swabs of commercial chickens from north India. Methods and Results: Escherichia coli isolates were assessed for susceptibility to 14 different antibiotics using the disc-diffusion technique and were screened for the presence of 22 antibiotic resistance genes (ARGs) by employing PCR. Isolates were found to be highly resistant to fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The ARGs in the integron can be arranged in different combinations [ 34 , 35 ]. It has been reported that the dfr ( dfr A16, dfr A17) + aad ( aad A1, aad A2, aad A5) gene family in the ARG boxes is the most common combination, encoding dihydrofolate reductase and aminoglyco adenosyltransferase, respectively [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ARGs in the integron can be arranged in different combinations [ 34 , 35 ]. It has been reported that the dfr ( dfr A16, dfr A17) + aad ( aad A1, aad A2, aad A5) gene family in the ARG boxes is the most common combination, encoding dihydrofolate reductase and aminoglyco adenosyltransferase, respectively [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its association with CRRs on ColV virulence plasmids, such as pCERC3 [ 37 ] in commensal E. coli from healthy humans [ 38 ], is concerning. sul3 , first described in E. coli from swine [ 39 ], has since been found to be globally distributed in swine [ 40 ], humans [ 34 ], poultry [ 41 , 42 ] and wild birds [ 43 ]. The gene forms part of a sul3 -encoding conserved segment ( sul3 -CS) that replaced the sul1 -containing 3′-CS that is typical of class 1 integrons [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all three isolates displayed mutations in the QRDR region of gyrA and parC , which has also been reported in many investigations. 30 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, all three isolates displayed mutations in the QRDR region of gyrA and parC, which has also been reported in many investigations. 30 The IncFII plasmids are highly mobile and carry several bla NDM variants in Enterobacteriaceae. 44 A recent study has shown the ability of bla NDM bearing IncFII plasmid transfer to different members of Enterobacteriaceae along with the other ARGs.…”
mentioning
confidence: 99%